Rationalizing epidemics : meanings and uses of American Indian mortality since 1600 - Jones, David S. (David Shumway) (Harvard University Press, 2004)
"In Rationalizing Epidemics, David Jones examines crucial episodes in this history: Puritan responses to Indian depopulation in the seventeenth century; attempts to spread or prevent smallpox on the Western frontier in the eighteenth and nineteenth centuries; tuberculosis campaigns on the Sioux reservations from 1870 until 1910; and programs to test new antibiotics and implement modern medicine on a Navajo reservation in the 1950s. These encounters were always complex. Colonists, traders, physicians, and bureaucrats often saw epidemics as markers of social injustice and worked to improve Indians' health. At the same time, they exploited epidemics to obtain land, fur, and research subjects, and used health disparities as grounds for "civilizing" American Indians. Revealing the economic and political patterns that link these cases, Jones provides insight into the dilemmas of modern health policy in which desire and action stand alongside indifference and inaction."--Jacket